The impacts of China's crops trade on virtual water flow and water use sustainability of the "Belt and Road". (1st December 2022) - Wei, Kexin; Ma, Chi; Xia, Jun; Song, Jinxi; Sun, Haotian; Gao, Junqing; Liu, Junguo
Abstract: Since the "Belt and Road" initiative was put forward, the trade of crops between China and the countries have increased markedly. Agriculture is the most water-consuming sector, the trade of crops could influence national water availability via virtual water embodied in the products. In order to gain an in-depth understanding of the water use of crops traded in countries along the "Belt and Road", from the perspective of import and export of China's crops, based on the characteristics and driving factors of virtual water trade, we proposed the Water Use Potential Index (WUPI) to assess sustainability of countries and their crops, and constructed a more comprehensive virtual water trade research framework. Results showed that the import and export of virtual water in 64 countries was dominated by green virtual water content from 2001 to 2017, and China was in a virtual water trade surplus. The Association of South-East Asian Nations was China's leading importer and exporter. The level of agricultural available water resources, the proportion of the agricultural population, the scale of agricultural production and the virtual water intensity could promote the growth of virtual water trade in crops between China and countries along the "Belt and Road", while economic model and the population structure played a restraining role. In terms of water use potential, China and Kazakhstan had great sustainable water use potential for crops, and the trade structure of other countries still needed to be further optimized. Understanding the virtual water trade in crops can provide a reference for the rational planning of crop cultivation and water resource conservation. Graphical abstract: Image 1 Highlights: Green virtual water content was the main contributor in the countries along the "Belt and Road". The Association of South-East Asian Nationswas China's leading importer and exporter. The level of agricultural available water resources could promote the growth of virtual water trade in crops. Crops in China and Kazakhstan were generally in line with the conditions of sustainable water use potential.